Pengaruh Jarak Tanam dan Takaran Pupuk Kandang Sapi terhadap Pertumbuhan dan Hasil Tanaman Wortel (Daucus carota L.) - Maria Desneri Fai (Fakultas Pertanian, Universitas Timor, 2018)
This study aims to determine the effect of spacing and dosage of cow manure on the growth and yield of carrot plants as well as knowing the spacing and dosage of cow manure that is appropriate for optimum growth and yield of carrots. The design used was factorial randomized block design (RBD) 3 x 3 which was repeated three times. The first factor is the spacing consisting of three levels, namely 10 cm x 10 cm, 10 cm x 20 cm and 10 cm x 30 cm. The second factor is cow manure dosage consisting of three levels, namely without fertilizer or 0 t / ha, 10 t / ha, and 15 t / ha. The results showed that the interaction between the spacing and doses of cow manure occurred on parameters of plant height 25 days after planting and tuber length. The spacing has a significant effect on soil temperature 70 days after planting, plant height 50 days after planting, fresh weight of tubers per plant, and fresh weight of stems, while cow manure doses did not significantly affect all observed parameters. Giving 15 t / ha cow manure dosage gave the highest yield of 129.57 t / ha, while the spacing of 10 cm x 30 cm gave the highest carrot yield of 139.66 t / ha.